PENGARUH PENYULUHAN TERHADAP PENGETAHUAN IBU BALITA TENTANG POSYANDU DI POSYANDU ASOKA V WILAYAH KERJA PUSKESMAS MEGANG KOTA LUBUKLINGGAU TAHUN 2020 - Siti Qoiriyah; Arie Anggraini; Novia Sari (Sekolah Tinggi Pariwisata Mataram, 2021)
Effort to decrease the number of mother’s death and the number of baby’s death, executive is not also trought KB programme but also healty’s programme. Effort in this cohesiveness is used to approach through development health community village, is executive operational is formed integrated service post (posyandu), most of them wichc unfunction and monitoring grouth only do about 30% from the number of children under 5 years there is the cause indirect happen the number of illness and children under 5 years death is attitude negative of mother in bebefit posyandu, so that children under 5 years health is not observed. This research is used quasi experiment design which aimed to know the influence of education health toword children under 5 years’s mother knowledge about posyandu in posyandu ASOKA V district work Puskesmas MEGANG Kota Lubuklinggau. The population in this research are parents which have children under 5 years which exist in Posyandu ASOKA V are 42 people. The technique to take the sanple throught purposive sampling technique. Data collecting is do through questioner content. This research is do on date 12-17 August 2015 data taht used in this research is primary data and secondary data. Data analysis is used is univariat and bivariat used uji paired T-test. The result of this research is pointed out is mayority children under five years mother’s knowledge not good about posyandu before use education health is about 21 (50%), after do education health is good mayority children under 5 years mother have enaugh knowledge is 22 (55,4%). From the result of test paired T-test got P-Value = 0,000. If P-Value < 0,05 so it can coucluded is there is an influence education health toward children under 5 years mother knowledge about posyandu in posyandu ASOKA V district work puskesmas Megang. It suggested > in under to children under 5 years mother can increased knowledge through the method to follow education health, get the information in social media and place health, and increased education to higher ladder.